Nördliches Eismeer, Ostküste von Island bis Norwegen / herausgegeben vom Reichs-Marine-Amt, 1910 - Germany. Reichs-Marine-Amt (Berlin : Reichs-Marine-Amt, 1929)
Kleine Berichtigungen: . 1929 Relief shown by hachures and spot heights. Depths shown by soundings and isolines.; "Nr. 108."; Includes abbreviation table and inset map of "Jan Mayen."; Selected lights colored in orange and yellow Color; 1:1,200,000